THE IMPORTANCE OF ARTIFICIAL INTELLIGENCE IN THE EDUCATION SYSTEM - Mansurova Ruxshona Shukurjon qizi (“SUN’IY INTELLEKTNING TIL O‘RGANISHDAGI O‘RNI” MAVZUSIDA TALABALAR ILMIY-AMALIY KONFERENSIYASI, 2025)
This article analyzes artificial intelligence (AI), which is currently becoming a key tool in the education system amid globalization, helping to create numerous opportunities among the students of the 21st century. AI is facilitating the implementation of many innovations, encouraging teachers to adopt an interactive approach to lessons, and providing the ability to translate books into any desired language. Additionally, this technology helps strengthen international relations and enables users to receive complete answers to complex questions.